Enhanced external counter pulsation therapy in patients with symptomatic and severe intracranial steno-occlusive disease: a randomized clinical trial protocol - Sharma, Vijay K.; Gopinathan, Anil; Tan, Benjamin Y. Q.; Loh, Poay Huan; Hung, Jennifer; Tang, David; Chua, Christopher; Chan, Amanda C. Y.; Ong, Jonathan J. Y.; Chin, Amanda; Jing, Mingxue; Goh, Yihui; et al. (Frontiers in Neurology, 2023)
Intracranial stenosis is prevalent among Asians and constitute a common cause of cerebral ischemia. While the best medical therapy carries stroke recurrence rates in access of 10% per year, trials with intracranial stenting have been associated with unacceptable peri-procedural ischemic events. Cerebral ischemic events are strongly related to the severity of intracranial stenosis, being high in patients with severe intracranial stenosis with poor vasodilatory reserve. Enhanced External Counter-Pulsation (EECP) therapy is known to improve myocardial perfusion by facilitating the development of collateral blood vessels in the heart. In this randomized clinical trial, we evaluate whether EECP therapy may be useful in patients with severe stenosis of intracranial internal carotid (ICA) or middle cerebral artery (MCA). The review of literature, methods of evaluation, status of currently used therapeutic approaches and trial protocol have been presented. Clinical Trial Registration: ClinicalTrials.gov, Identifier: NCT03921827.